Everything you need to know about rheumatic fever - Margulies, Phillip, 1952- (New York : Rosen Pub. Group, 2004)
Presents an overview of rheumatic fever that includes the history of the disease, new developments in combating it, and new ways to prevent its spread.
Includes bibliographical references and index.
Keywords: Rheumatic fever -- Juvenile literature; Rheumatic fever; Diseases